Analysis of The Implementation of Electronic Medical Records Using the Human Organization Technology FIT Model - Faradisa Fauziyah, Nida; Nurhayati, Asti; Ulum Mahfud, Miftakhul (Syntax Corporation, 2025)
The use of electronic medical records (EMRs) in healthcare has transformed the way patient information is stored and shared among healthcare providers. Because of the importance of electronic medical records, several aspects are needed for the ERM to function well. The human organization and technology factors are some of the necessary elements for the successful implementation of electronic medical records. Human Organization Technology Fit Model is a framework that helps healthcare organizations assess how well their employees, processes, and technology systems work together to achieve their goals. Objective: The purpose of this research is to determine the relationship between human organization and technology in the implementation of electronic medical records in hospitals. This research is a descriptive study using quantitative methods and research uses questionnaires. The research was conducted in several private hospitals, population consists of all EMRs users in outpatient care, which amounts to 132 staff members. This research used non-probability sampling technique. The data analysis will be conducted using Spearman tests with interval data scale, aided by the SPSS. There is a relationship between human and organization (p<0.001) with a strong relationship, as indicated by a r=0.686. There is relatioship between human and organization (p<0.001), It has a strong relationship, as indicated by a r=0.683. Between organization and technology have relationship (p< 0.001) with a very strong correlation r=0.809. The utilization of electronic medical records and human organization technology are related. Keywords: EMRs, Human, Organization, Technology, Implementation